A Prospective Study on Risk Factors for Acute Kidney Injury and All-Cause Mortality in Hospitalized COVID-19 Patients From Tehran (Iran) - Rostami, Zohreh; Mastrangelo, Giuseppe; Einollahi, Behzad; Nemati, Eghlim; Shafiee, Sepehr; Ebrahimi, Mehrdad; Javanbakht, Mohammad; Saadat, Seyed Hassan; Amini, Manouchehr; Einollahi, Zahra; Beyram, Bentolhoda; Cegolon, Luca (Frontiers in Immunology, 2022)
Background. Several reports suggested that acute kidney injury (AKI) is a relatively common occurrence in hospitalized COVID-19 patients but its prevalence is inconsistently reported across different populations. Moreover, it is unknown whether AKI results from a direct infection of the kidney by SARS-CoV-2 or it is a consequence of the physiologic disturbances and therapies used to treat COVID-19. We aimed to estimate the prevalence of acute kidney injury (AKI) since it varies by geographical settings, time periods and populations studied; and to investigate whether clinical information and laboratory findings collected at hospital admission might influence AKI incidence (and mortality) in a particular point in time during hospitalization for COVID-19. Methods. Herein we conducted a prospective longitudinal study investigating the prevalence of AKI and associated factors in 997 COVID-19 patients admitted to Baqiyatollah general hospital of Tehran (Iran), collecting both clinical information and several dates (of: birth; hospital admission; AKI onset; ICU admission; hospital discharge; death). In order to examine how the clinical factors influenced AKI incidence and all-cause mortality during hospitalization, survival analysis using the Cox proportional-hazards models was adopted. Two separate multiple Cox regression models were fitted for each outcome (AKI and death). Results. In this group of hospitalized COVID1-19 patients, prevalence of AKI was 28.5% and the mortality rate was 19.3%. AKI incidence was significantly enhanced by diabetes, hyper-kalemia, higher levels of WBC count and blood urea nitrogen (BUN). COVID-19 patients more likely to die over the course of their hospitalization were those presenting a joint association between ICU admission with either severe COVID-19 or even moderate COVID-19, hypo-kalemia, higher level of BUN, WBC and LDH measured at hospital admission. Diabetes and comorbidities did not increase the mortality risk among these hospitalized COVID-19 patients. Conclusions. Since the majority of patients developed AKI after ICU referral and 40% of them were admitted to ICU within 2 days since hospital admission, these patients may have been already in critical clinical conditions at admission, even though affected by mild/moderate form of COVID-19, suggesting the need of early monitoring these patients for the onset of eventual systemic complications.